Pengaruh Stres Kerja, Kepemimpinan Digital Dan Knowledge Sharing Terhadap Perilaku Kerja Inovatif Yang Dimediasi Oleh Kepuasan Kerja (Studi Kasus Pada Karyawan Tetap PT. Awana Sawit Lestari) - Ramadhani, Indah Nur; Slamet, Afi Rachmat; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study was conducted on permanent employees of PT Awana Sawit Lestari. The purpose of this research is to examine and analyze the influence of Job Stress, Digital Leadership, and Knowledge Sharing on Innovative Work Behavior, with Job Satisfaction as a mediating variable. This study employs a quantitative approach using a saturated sampling method with 114 respondents. Data was collected through questionnaires and analyzed using the SEM-PLS method with SmartPLS version 4. The analysis includes the outer model (Convergent Validity, Discriminant Validity and Composite Reliability), inner model (R2 and Q2) and Hypothesis Testing. The results show that Job Stress does not affect Job Satisfaction, while Digital Leadership and Knowledge Sharing have a significant impact on Job Satisfaction. Additionally, Job Stress and Knowledge Sharing do not directly influence Innovative Work Behavior, whereas Digital Leadership has a positive impact on Innovative Work Behavior. Furthermore, Job Satisfaction does not mediate the relationship between Job Stress, Digital Leadership, and Knowledge Sharing on Innovative Work Behavior. Keywords: Work Stress, Digital Leadership, Knowledge Sharing, Innovative Work Behavior, Job Satisfaction.